Efficacy of Some Essential Oils that Have The Potential as Vegetable Feromones in Heterogeneous Croping Using The Trap Method - Erfandari, Ovy; Hamdani, Hamdani; Wahyuningsih, Eka (Jurnal Biologi Tropis, 2024)
The use of pheromones as traps is often used to control various pest. Pheromones that are widely used today usually contain chemical ingredients which in the long term can certainly affect the environment and pest populations the. Pheromones made from essential oils are not widely used controlling pests. In order to formulate and apply the IPM concept it is necessary Testing the efficacy of several combinations of essential oils that have the potential to act as pheromones was carried out vegetable crops to implement pest control based on Integrated Pest Management (IPM). It is hoped that it will be possible to use pheromones derived from essential oils means in the process of controlling pests on plantation crops and commodities other plants and can also be integrated with pest control methods other integrated (PHT). This research was conducted using a randomized design complete (RAL) consisting of 6 (six) treatments which were repeated 3 times. Thus there are 18 (eighteen) experimental sample points. Treatment consists of use of vegetable pheromones derived from patchouli oil, cinnamon oil, oil nutmeg, clove oil, control (water) and combination (all treatments). Research data which was analyzed using Analysis of Variance (ANOVA) followed by a Real Difference test The smallest (BNT) with a significance level of 5% shows that patchouli oil has potential as a vegetable pheromone because it can trap 85 insect/non-insect organisms insect. Based on the results of identifying trapped organisms, insects from the order Diptera were the most dominant in each treatment.